Emergency Medicine Teaching of Undergraduate Medical Students in Iraq: A Call for Review of The Current Status - Al-Mansouri, Loma A.; AL-Obaidi, Firas R. (Scientific Journal of Medical Research, 2020)
Aims of this document are developing emergency medicine curriculum model for undergraduate medical students through defining the basic requirements of that curriculum. Encourage review of the current educational process of emergency medicine in Iraq and the system of evaluation and assessment of students. The teaching of emergency medicine is considered now a cornerstone in the medical education and the updates and developments in this field necessitate reconsideration of the methodology and curriculum applied in our universities. The suggestions proposed in this paper can be first step toward renovation of emergency medicine teaching in Iraq.